Keefektifan model search, solve, create, and share ditinjau dari prestasi, penalaran matematis, dan motivasi belajar - Rody Satriawan (Program Studi Pendidikan Matematika Program Pascasarjan Universitas Negeri Yogyakarta, 2017)
Tujuan penelitian ini adalah untuk mendeskripsikan keefektifan pembelajaran matematika dengan model search, solve, create, and share (SSCS) dan apakah pembelajaran matematika dengan model SSCS lebih baik dibandingkan dengan model konvensional ditinjau dari prestasi, penalaran matematis, dan motivasi belajar. Penelitian ini merupakan penelitian eksperimen semu dengan desain kontrol grup non-ekuivalen. Populasi dalam penelitian adalah seluruh siswa kelas VIII SMP Muhammadiyah Banguntapan yang terdiri dari lima kelas. Sampel penelitian diambil dua kelas secara acak, yaitu kelas VIII-D dan VIII-E. Analisis data yang digunakan adalah uji T2 Hotteling’s, uji MANCOVA, dan uji lanjut dengan prosedur t-test. Setiap analisis dilakukan pada taraf signifikansi 5%. Hasil penelitian ini adalah pembelajaran matematika dengan model SSCS efektif ditinjau dari prestasi dan motivasi belajar, tetapi tidak efektif ditinjau dari penalaran matematis siswa dan pembelajaran matematika dengan model SSCS lebih baik dibandingkan dengan pembelajaran konvesional ditinjau dari prestasi dan penalaran matematis, tetapi tidak lebih baik ditinjau dari motivasi belajar siswa kelas VIII SMP Muhammadiyah Banguntapan.Kata Kunci: model SSCS, model konvensional, prestasi belajar, penalaran matematis, motivasi belajar siswa The Effectiveness of the Model of Search, Solve, Create, and Share Terms of Achievement, Mathematical Reasoning, and Motivation to Learn AbstractThe purpose of this study is to describe the effectiveness of teaching with the teaching model search, solve, create, and share (SSCS) and to describe whether teaching by teaching model SSCS better than by model conventional regarding students’ achievement, mathematical reasoning, and mathematics learning motivation. This research was quasi-experimental with the non-equivalent control group design. The population was all students of class VIII SMP Muhammadiyah Banguntapan consisting of five classes. The sample taken at random consisted of two classes: classes VIII-D dan VIII-E. Class VIII-D was taught by using the model conventional, while class VIII-E was taught by using the SSCS teaching model. The data were analyzed by using a multivariate test Hotelling's T2, MANCOVA test, and tested further by using t-test procedures. Each analysis regarding at the significance level of 5%. The results showed that: the first, the teaching of mathematics by using the SSCS model is effective regarding students’ achievement and students’ mathematics learning motivation, but it is not effective in terms of mathematical reasoning Banguntapan Muhammadiyah junior high school students of class VIII. The second, the SSCS teaching model is better than the conventional teaching model regarding students’ achievement and mathematical reasoning abilities, but not better terms of students’ mathematics learning the mathematics of class VIII SMP Muhammadiyah Banguntapan.Keywords: teaching model of SSCS, teaching model of conventional, academic achievement, mathematical reasoning ability, mathematics learning motivation